Proposta de roteiro estratégico para implantação de teletrabalho em organizações públicas: um estudo de caso no Ministério Público do Trabalho - Heringer, Valério Soares (2017)
Teleworking is a type of labor activity developed in a different location from the employers or service provider’s address; and for its carrying out there are information technology and communication tools for the production, storage or exchange of results. The general objective of this essay is the introduction of a strategic roadmap proposal for the implanting of telework in the public sector which adopts the management model based on planning and strategic management. For that reason, the research had specific goals such as: characterization of telework with its origin identification, concept, evolution process, typology, technology determining factors organizational processes, socio-professional relations, contextualization of telework in the present Brazilian public sector, identification of key factors for the success of implanting telework in the public sector which adopts the management model based on planning and strategic management, data collection and the description of management transformation process and technology development in the Public Labor Works from 2007-2017, signaling aspects that made implanting telework in the institution possible, understandingthe conceptual basis of oadmapping, making sure it is adaptable to government services process and promoting adequate means for building the roadmap of implementing telework in the public sector; indicating future tendencies of telework in public works. The objects of research were submitted to the inductive method, having used bibliography research and case studies in data collection, the latter containing document research, participative notes,descriptive research and interview. Results and Conclusions: Bibliography survey revealed that the tendency to telework and automatization of certain activities has been growing and it has shown risk to future generations of work stations in different areas of industry, sales and services. Management sector, where the State is mostly present, shall undergo major changes in its service processes in the next two decades, with the probable reduction of its physical and functional structures. Document research shows that from 2006 on, a growing number of public organizations have been implementing telework programs in order to increase productivity, reduce operational costs, promote social inclusion, contribute with environment sustainability and improve employees’ quality of life. The tendency is a rapid growth of these flexible types of work, as it is already happening in the private sector. Processes of implementing telework programs present different degrees of complexity depending on size of organization and ability to generate, move and store digital assets. For the public sector, when interested in instituting telework programs, the budget, motivation of leaderships and planning are determining factors. When a strategic plan is in course, it becomes necessary to form an inter-department board in 9 charge of elaborating the telework implementation project and the management changes plan,aligned with the organization’s strategy. In this essay we have introduced and discussed an ample set of policies in five different dimensions: planning and management; organization processes; information and communication technologies; people and rules management – related amongst each other and consolidated into a roadmap for implementation of telework adaptable to the public sector of any size or to service providers. Considering that in this research telework was approached on a predominantly functional perspective, additional studies shall analyze better management issues and leaderships in telework groups, especially regarding trust, an issue that concerns management of remote teams as well as to verify in the budget-financial field, the decrease or not, of costs and expenses, and different productivity levels between teleworkers and on-site workers.